(untitled) (Journal of Oriental Studies, 2021)
The article examines the evolution of the formation of the CCP’s power doctrine under the leadership of Xi Jinping, as well as the main concepts and principles. The main aspects of the theory of "socialism with Chinese characteristics in a new era" and the ideas of Xi Jinping are analyzed, new features of socialism and the innovative path of China, the ideology of classical Marxism are analyzed. It also examines the strategic domestic and foreign policy of the People’s Republic of China to implement the "Great Revival of the Chinese Nation" and "China Dream" through the implementation of ideological and economic megaprojects that contribute to the global process.